Enhanced Adsorptive Removal of Chromium (VI) from Aqueous Solution on Using Aged Refuse: Resource Recovery and Environmental Applications - B. Manimekalai; S. Sivanesan; P. Senthil Kumar (Adsorption Science & Technology)
“Aged refuse” corresponds to municipal solid waste material dumped in land, for several years. This solid waste material is chosen as an adsorbent for the current study since it is available abundantly in the state of Tamil Nadu, India, and has not been used for any other applications. The current study was conducted to get rid of the element chromium (VI) from wastewater by using the adsorption process. The aged refuse was analytically tested through various processes such as BET, TGA, XRD, SEM, and FTIR to determine the surface morphology, functional groups, thermal stability, nature of the crystalline, and surface area. The researchers conducted the batch adsorption study to validate the influence exerted by different sorts of adsorption parameters like contact time (10-100 min), initial concentration of the pollutant (50 mg·L-1 to 250 mg·L-1), pH (1-7), and the dosage of the adsorbent (0.5 g·L-1-3.0 g·L-1). In the current study, the researchers achieved the maximum adsorption capacity of 195.54 mg·g-1. From the kinetic results, it can be understood that the pseudo-first-order model was the most suitable kinetic model. Further, the study outcomes confirm that the Langmuir isotherm model is the best fit by isotherm studies which indicate the monolayer adsorption process. This study indicated that the aged refuse can be potentially used in removing Cr (VI) from water environment under standard optimized conditions.